2013
DOI: 10.1039/c3fo60216h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium-enriched exopolysaccharide produced by Lactococcus lactis subsp. lactis on signaling molecules in mouse spleen lymphocytes

Abstract: Selenium-enriched exopolysaccharides (Se-EPS) produced by Lactococcus lactis subsp. lactis can be used as a safe and effective selenium (Se) supplement. Analysis of the Se content and monosaccharide components of Se-EPS demonstrated that it consisted of mannose, fucose, ribose, glucose, galactose, and arabinose with a molar ratio of 5.48 : 0.39 : 9.77 : 4.03 : 1.00 : 1.92, and an Se content of 183.263 μg g(-1). The differing effects of Se-EPS and EPS on calcium channels and certain key secondary messengers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Crude extracts were mixed with isopyknic RPMI 1640 medium, aer which lymphocytes were pelleted by centrifugation at 1500 g for 10 min at 4 C. RPMI 1640 medium was then added to obtain the lymphocyte suspension. 20…”
Section: Isolation Of Mice Lymphocytesmentioning
confidence: 99%
“…Crude extracts were mixed with isopyknic RPMI 1640 medium, aer which lymphocytes were pelleted by centrifugation at 1500 g for 10 min at 4 C. RPMI 1640 medium was then added to obtain the lymphocyte suspension. 20…”
Section: Isolation Of Mice Lymphocytesmentioning
confidence: 99%
“…Many EPS-producing LAB species have been isolated and identified, including Streptococcus thermophilus (Lemoine et al, 1997), Lactococcus lactis (Liu et al, 2013), L. casei, L. rhamnosus, L. plantarum, Lactobacillus delbrueckii subsp. bulgaricus, Lactobacillus brevis, Lactobacillus curvatus, Lactobacillus helveticus, Lactobacillus johnsonii (Oleksy and Klewicka, 2018), and Lactobacillus fermentum (Ale et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes play an important role in the immune responses and the activation of lymphocytes is related with the proliferation and release of cytokines (Liu et al . ). Previous research indicated that some bacterial EPS can influence the lymphocyte population and cytokine production pattern (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous research indicated that some bacterial EPS can influence the lymphocyte population and cytokine production pattern (Liu et al . ; Hidalgo‐Cantabrana et al . ; Matsuzaki et al .…”
Section: Discussionmentioning
confidence: 99%